2023
DOI: 10.5829/ije.2023.36.03c.11
|View full text |Cite
|
Sign up to set email alerts
|

Growth Media Optimization for Production of Alkaline Protease from Industrial Wastewater using Bacillus subtilis PTCC 1254

Abstract: Alkaline proteases are widely used in industrial processes due to their high pH tolerance and thermal stability. In present work, the protease producing ability of Bacillus strains (Bacillus subtilis PTCC 1254, B. subtilis PTCC 1156 and B. subtilis PTCC 1715) was studied. B. subtilis PTCC 1254 showed the highest proteolytic activity and therefore, the strain was selected as the biological agent in the submerged fermentation. Cell growth kinetic model was investigated using Malthus and Logistic equations, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…JKSP1. A closer temperature of 37 o C (88.14 U/mL) enhanced the protease activity of Bacillus subtilis PTCC1254 isolated from wastewater as reported by Jafari et al [16]. However, a lower temperature of 20 o C enhanced the protease production of Bacillus sp.…”
Section: Temperaturesupporting
confidence: 50%
See 2 more Smart Citations
“…JKSP1. A closer temperature of 37 o C (88.14 U/mL) enhanced the protease activity of Bacillus subtilis PTCC1254 isolated from wastewater as reported by Jafari et al [16]. However, a lower temperature of 20 o C enhanced the protease production of Bacillus sp.…”
Section: Temperaturesupporting
confidence: 50%
“…Researchers have reported Bacillus species for protease production. Jafari et al [16] identified Bacillus subtilis PTCC 1254 isolated from wastewater as a potent protease producer. Hashmi et al [14] also identified Bacillus subtilis S1 and Bacillus amyloliquefaciens KSM12 as the two highest protease-producing microbial strains from soil habitats.…”
Section: Identification and Gene Detection Of Protease-producing Bact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that in most cultivation conditions, species of Bacillus , like Bacillus subtilis , produce extracellular alkaline proteinases during the late exponential and stationary phases of batch culture growth ( Singh et al, 2004 ; Zhou et al, 2019 ; Jafari et al, 2023 ). This pattern aligns with the consistency observed in our study, both before and after the optimization of the medium and fermentation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other microbial species, such as Pseudomonas aeruginosa ( Saleem, 2012 ), also exhibit similar fermentation patterns when synthesizing alkaline proteases. The model demonstrates that in Bacillus fermentation processes with shorter cycles (10–30 h), the peak activity of alkaline protease occurs 2–12 h after the point of maximum biomass ( Singh et al, 2004 ; Subba Rao et al, 2009 ), while in longer fermentation cycles (60–80 h), the peak activity of alkaline protease lags behind the time of highest cell density by 30–38 h ( Saleem, 2012 ; Jafari et al, 2023 ). However, the stage of the cell growth cycle at which extracellular protease synthesis reaches its maximum has been a topic of ongoing debate.…”
Section: Discussionmentioning
confidence: 99%